1996
DOI: 10.1093/clinids/23.5.1081
|View full text |Cite
|
Sign up to set email alerts
|

High Rate of Nasopharyngeal Carriage of Potential Pathogens Among Children in Greenland: Results of a Clinical Survey of Middle-Ear Disease

Abstract: Nasopharyngeal and middle-ear colonization with bacteria and viruses, including Mycoplasma pneumoniae and chlamydiae, was investigated in a survey of 54 children with acute otitis media (AOM) and 201 control children without AOM in Greenland. In total, 98% with AOM and 91% without AOM carried potentially pathogenic bacteria in the nasopharynx. Two or more potentially pathogenic species were carried by 78% with AOM and 57% without AOM. Haemophilus influenzae was found in 92% and 77%, respectively, but only Stre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
46
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(47 citation statements)
references
References 39 publications
0
46
1
Order By: Relevance
“…It may cause various respiratory tract infections such as pharyngitis, croup, tracheobronchitis, and bronchiolitis besides pneumonia. Some data showed that the presence of M. pneumoniae in the upper respiratory tract was common in asymptomatic children, while others indicated that there was no evidence of asymptomatic carriage (6)(7)(8).…”
mentioning
confidence: 99%
“…It may cause various respiratory tract infections such as pharyngitis, croup, tracheobronchitis, and bronchiolitis besides pneumonia. Some data showed that the presence of M. pneumoniae in the upper respiratory tract was common in asymptomatic children, while others indicated that there was no evidence of asymptomatic carriage (6)(7)(8).…”
mentioning
confidence: 99%
“…This supports the idea that Aborigine populations are colonised by variants of nasopharyngeal commensals with which they have not co-evolved, and to which they may not have the genetic repertoire to mount a directed and specific immune response. More frequent and more dense nasopharyngeal colonisation by otopathogens has also been documented in the Inuit (Homoe et al 1996b).…”
Section: Ethnic Variations In Otitis Media Incidencementioning
confidence: 88%
“…Persistent carriage was more frequent with these types. On the other hand, persistent nasopharyngeal carriage of single strains was serotype-dependent 6,14,19,23 and occurred more commonly between 5 and 8 months of age. The duration of carriage decreased with the carriage of successive pneumococcal serotypes and hence was inversely correlated with age.…”
Section: Discussionmentioning
confidence: 97%
“…Our findings supports earlier studies from similar centers over the last decade. [9][10][11][12][13][14][15][16][17][18][19][20][21] Recent research established daycare attendance as an important factor influencing the epidemiology of many infectious diseases. [26][27][28] A number of studies have demonstrated a strong association between daycare attendance and increased carriage of S. pneumoniae, especially of resistant strains.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation